2023
DOI: 10.1177/17540739231214533
|View full text |Cite
|
Sign up to set email alerts
|

Collective Emotion: A Framework for Experimental Research

Victor Chung,
Julie Grèzes,
Elisabeth Pacherie

Abstract: Research on collective emotion spans social sciences, psychology and philosophy. There are detailed case studies and diverse theories of collective emotion. However, experimental evidence regarding the universal characteristics, antecedents and consequences of collective emotion remains sparse. Moreover, current research mainly relies on emotion self-reports, accounting for the subjective experience of collective emotion and ignoring their cognitive and physiological bases. In response to these challenges, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 168 publications
1
1
0
Order By: Relevance
“…First, we provide evidence refining the conceptual model of collective effervescence (Rimé & Páez, 2023) and notably the role of physiological arousal in fostering different prosocial attitudes. Second, our study shows a possible decoupling between objective measures of shared emotions (the convergence and synchronization of emotional responses) and the subjective experience of sharing (mutual feelings of connectedness), which suggests the existence of independent and possibly additive mechanisms of social bonding during shared experiences (Chung et al, 2023). These results support the idea that shared emotional experiences represent a continuum that ranges from weakly to strongly shared emotions (Thonhauser, 2022;Salmela, 2012).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…First, we provide evidence refining the conceptual model of collective effervescence (Rimé & Páez, 2023) and notably the role of physiological arousal in fostering different prosocial attitudes. Second, our study shows a possible decoupling between objective measures of shared emotions (the convergence and synchronization of emotional responses) and the subjective experience of sharing (mutual feelings of connectedness), which suggests the existence of independent and possibly additive mechanisms of social bonding during shared experiences (Chung et al, 2023). These results support the idea that shared emotional experiences represent a continuum that ranges from weakly to strongly shared emotions (Thonhauser, 2022;Salmela, 2012).…”
Section: Discussionsupporting
confidence: 74%
“…Shared emotion can be defined as an interpersonal pattern of emotions that emerges at grouplevel (von Scheve & Salmela, 2014;Salmela, 2012;Goldenberg et al, 2020). Notably, previous research identified several cognitive mechanisms that are responsible for the convergence (similarity in form and content) and the synchronization (similarity in time course) of emotions between individuals (Chung et al, 2023;Wood et al, 2021;Parkinson, 2020;von Scheve & Ismer, 2013). During social interactions, convergence and synchronization can result from reciprocal influence between individuals, i.e., interpersonal alignment (Butler, 2011;Dumas & Fairhurst, 2021).…”
Section: Introductionmentioning
confidence: 99%